DIABETES-ASSOCIATED OSTEOARTHRITIS: A SYNTROPY? - E. V. Kazygasheva (SPb RAACI, 2016)
This review presents our own and literature data dedicated to predisposing and pathogenetic factors involved in development of a common comorbidity, diabetes-associated osteoarthritis (DAOA). So far, there is no wide-accepted clinical or scientific viewing of DAOA as a distinct clinical phenotype of osteoarthritis (OA). To our knowledge, the role of genetic factors in DAOA development was not discussed in details. Therefore, we have drawn attention to the cross-acting genes involved in both OA and diabetes, i.e., PPARγ, FTO, ADIPOQ, and AGE. These genes encode proteins which can contribute to the pathogenesis of both OA and diabetes. However, some controversies exist about genetic predisposal for OA and diabetes. We review the studies which concern various clinical characteristics of DAOA. We describe a role of chronic hyperglycemia, insulin resistance, advanced glycation end-products (AGE) in development of OA and micro- and macrovascular complications of diabetes. The mechanisms of low-grade inflammation, humoral and cellular immune responses to cartilage antigens, and their role in OA progression are discussed. We underline a similarity of low-grade inflammation in OA and microvascular complications in diabetes. In conclusion, OA and diabetes comorbidity is not a mere coincidence of these diseases. They share some common genetic and pathogenetic factors, a distinct phenotype, and may change thinking of physicians and scientists towards a holistic (personalized) approach to prevention, diagnosis, treatment and prognosis of this comorbidity. We discuss opportunities of DAOA pharmacotherapy based on the key comorbidity feature, i.e., emergence of a new disease property by coexistence of several diseases. One may hypothesize that studying genetic, molecular, and cellular networks in comorbidities may lead to new treatment strategies (‘network pharmacology”) based on targeting the network hubs. We provide examples of such approach in some polypathies (e.g., phenofibrate, a PPARα agonist; simvastatin, a GMGCoA reductase in OA, rheumatoid arthritis and psoriasis), and its potential discuss usefulness is discussed for DAOA. In particular, we provide an example of a pilot study of ademethionine, a methyl group donator.